Ergonomic Risk and Musculoskeletal Disorders in Rice Farmers at Karang Tanjung Village, Karawang Regency - Rahdiana, Nana; Suhardiman, Sani; Sukarman, Sukarman (Universitas Ahmad Dahlan, 2022)
This study discussed musculoskeletal risk analysis related to ergonomics, occupational safety, and health in agriculture in the Karawang district. Musculoskeletal Disorders (MSDs) are occupational diseases that cause pain in the joints. The working position of rice farmers, especially during planting rice seeds and harvesting rice, is not suitable for ergonomics. This study aims to identify the MSDs experienced by farmers in Karang Tanjung village, Karawang district. The study used an analytical method using the Nordic Body Map (NBM) and RULA questionnaires to assess work posture. A sample of 30 workers was chosen for an observational cross-sectional study. The results showed that the ergonomic risk level entered level 4 in the high category. The most dominant MSDs felt by rice farmers in Karang Tanjung village were the waist (98%) and the neck (95%). This research was expected to serve as a model for future musculoskeletal risk reduction research.